Phoenix roebelenii: Pygmy Date Palm - Timothy K. Broschat (EDIS)
The pygmy date palm is one of the most popular small landscape palms in Florida. It is single-stemmed, but is often grown in clumps of 2–4 closely spaced individuals which, when older, give the impression of a multi-stemmed palm. This revised 4-page fact sheet was written by Timothy K. Broschat and published by the UF Department of Environmental Horticulture, August 2014.